The Nucleic Acid Amplification Test in Pulmonary Diseases - Nurwidya, Fariz; Bies, Asri Liqditta; Winardi, Wira; Harinda, Fadlika (Journal Of Health Science (Jurnal Ilmu Kesehatan), 2024)
Nuclei as a cell nucleus have been found since the 18th century. This discovery was then developed for the need for methods for diagnosing pathogenic organisms of an infectious disease at that time. The aim of this study is to review the principle of nucleic acid amplification test and describe the existing evidence regarding the role of the test in respiratory diseases. The study use the keywords, such as nucleic acid, diagonsis and nucleic acid amplification test, to invesitage relevant studies in PubMed and Google Scholar database. We found that nucleic acid-based testing techniques have evolved to adapt to the need for early and rapid detection and rely on a high level of accuracy. This continuously developed technology can replace conventional test methods. Conventional examination is known to take longer time so the definitive therapeutic might be delayed. However, there is still an obstacle, namely the cost of tests quite expensive because of the standard procedure that must be strictly followed, otherwise result might not be valid. The technique from the beginning needs to be carried out following the procedure, starting with the preparation of tools, how to take samples, how to deliver the samples to the laboratory, and how to process and analyze data. This procedure is necessary to minimize false positive or negative results. As a conclusion, nucleic acid assays is beneficial in pulmonary infectious diseases diagnosis, however it is high-cost and not recommended for treatment evaluation in pulmonary infection.